Comparative flexural performance of steel fibre reinforced self-compacting concrete (SCFRC) ribbed slab with different fibre provision area - Hazrina Ahmad; Mohd Hisbany Mohd Hashim; Afidah Abu Bakar; Fariz Aswan Ahmad Zakwan; Ruqayyah Ismail (Acta Polytechnica CTU Proceedings, 2022)
The flexural performance of three SCFRC ribbed slabs with different fibre provision area were investigated in this paper; in both ribs and flange (SFWS), ribs only with additional welded mesh in flange (SFT) and in ribs only (SFR). Short hooked end fibres of 35 mm length of 1% volume fraction was blended with the flowable self-compacting concrete (SCC) were used as the material for the slabs. Slab samples of 2.8 × 1.2 × 0.2 m were constructed and loaded until failure under four- point bending. Investigation was carried out in view of the load bearing capacity, deflection, energy absorption capacity as well as the failure modes. The influence of the steel fibre provision on the strain distribution was also examined.